Factors determining L2 learning motivation in higher education: Impacts of L2 related training and outcome requirements (Training and Practice : Journal of Educational Sciences, 2023)
Following a recent announcement by the Hungarian Government, higher education institutions have been given the freedom to decide whether from 2024 onwards they wish to continue requiring their students to obtain the formerly mandatory (specific purposes) foreign language examination as a requirement for degree award. To investigate the current and the foreseeable potential future impacts of the currently compulsory foreign language exams on L2 learning motivation, a questionnaire survey among university students studying ESP (N=1052) was carried out. The purpose of the study was to reveal the potential impact of L2 learning experience, the range of available L2 courses at university, ideal L2 self and willingness to take L2 exams on L2 learning motivation. Results show that language learning experience, the range of available L2 courses, ideal L2 self and willingness to take L2 examinations are predictors of motivated L2 learning behaviour in L2 classes. In addition, motivated L2 use in real-life situations outside the L2 classroom is influenced by the ideal L2 self, range of available L2 courses and language learning experiences, and is negatively influenced by willingness to take L2 examinations.
Keywords: foreign language learning motivation; language exam; willingness to take a language exam; language learning experiences; higher education; quantitative research; second language self system